Safety and quality control of transport services on railway transport - Sadlovska, I. P.; Sokolova, V. V. (Science and Transport Progress, 2011)
The article presents the provisions to improve procedure of licensing of passenger and freight transportation, technical specifications for services related to the passenger and freight transportations.